2002
DOI: 10.1093/humrep/17.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome and thrombophilia

Abstract: Molecular risk factors of hereditary thrombophilia do not show increased prevalence in women with PCOS in comparison with women in the general population. The existence of a possible trend towards higher prevalence of MTHFR mutation in women with PCOS needs further study, particularly regarding homocysteine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
3
27
2
3
Order By: Relevance
“…Although Tsanadis et al reported that the odds ratio for bearing a mutation on the methylene tetrahydrofolate reductase gene was 1.2-fold higher in women with PCOS than those without it, the mild elevation of the homocysteine levels in our PCOS patients are lower then expected as those of congenital enzymatic deficient patients could be [23].…”
Section: Discussioncontrasting
confidence: 65%
“…Although Tsanadis et al reported that the odds ratio for bearing a mutation on the methylene tetrahydrofolate reductase gene was 1.2-fold higher in women with PCOS than those without it, the mild elevation of the homocysteine levels in our PCOS patients are lower then expected as those of congenital enzymatic deficient patients could be [23].…”
Section: Discussioncontrasting
confidence: 65%
“…Thus a number of studies have investigated homocysteine and folate metabolism and confirmed the presence of increased serum homocysteine concentration in obese as well as in non-obese PCOS patients (Yilmaz et al, 2005). MTHFR polymorphism does not seem to be more frequent in these patients than in healthy controls (Tsanadis et al, 2002), and the possible determinants of elevated homocysteine concentration are still debated among authors who found significant correlations between homocysteine and insulin resistance or hyperandrogenism (Yarali et al, 2001;Schachter et al, 2003;Vrbikova et al, 2003;Bayraktar et al, 2004;Wijeyaratne et al, 2004) and those who did not (Loverro et al, 2002;Kilic-Okman et al, 2004;Yilmaz et al, 2005). Interestingly, administration of insulin sensitizers, such as metformin, as it is proposed in PCOS patients to improve ovulation induction and other parameters (Stadtmauer and Oehninger, 2005), has led to a further increase of serum homocysteine in these patients, despite the decrease in insulin resistance (Vrbikova et al, 2002;Kilicdag et al, 2005b).…”
Section: Folate Metabolism and Polycystic Ovary Syndromementioning
confidence: 95%
“…Cases of PCOS cluster in families revealed hereditability of both hyperandrogenaemia and hyperinsulinaemia in affected siblings [3,4]. It has been suggested that PCOS may be a thrombophilic state, although the differences were not statistically significant in a comparison study of women with PCOS and positive family history of thrombosis with the control group [5,6].…”
Section: Introductionmentioning
confidence: 97%